2015
DOI: 10.1039/c5ra03897a
|View full text |Cite
|
Sign up to set email alerts
|

Composite flocculants based on magnesium salt–polydiallyldimethylammonium chloride: characterization and flocculation behaviour

Abstract: This study describes preparation, characterization and examines flocculation characteristic of novel magnesium salt polydiallyldimethylammonium chloride (polyDADMAC) composite flocculants. Five different compositions have been prepared by physical blending between synthesized polyDADMAC and magnesium salt. Fourier transform infrared spectroscopy (FTIR) , intrinsic viscosity and zeta potential measurement were conducted to characterize the properties of the composite flocculants produced. Meanwhile jar test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Therefore, inorganic–organic hybrid or composite polymers have been synthesized to bond inorganic microparticles and organic electrolytes so they can be added simultaneously to the flocculation process. Recently, aluminum‐ and iron‐based flocculants have been widely used in water treatment applications, and it has been shown that they can improve flocculation compared to conventional flocculants …”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, inorganic–organic hybrid or composite polymers have been synthesized to bond inorganic microparticles and organic electrolytes so they can be added simultaneously to the flocculation process. Recently, aluminum‐ and iron‐based flocculants have been widely used in water treatment applications, and it has been shown that they can improve flocculation compared to conventional flocculants …”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
“…The hybrid composite flocculants with 30 and 70 wt% MgCl 2 could flocculate 2 wt% kaolin suspensions more efficiently than poly(DADMAC), and also reduced the turbidity of the supernatant more efficiently. Normally, poly(DADMAC) flocculates suspended particles through charge neutralization and bridging, but adding MgCl 2 salt in the composite flocculant enhanced its surface charge neutralization ability . The authors proposed that MgCl 2 acted as a secondary destabilizer and neutralized some of the very fine suspended particles.…”
Section: Recent Advances In the Development Of Water Soluble Flocculantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it is possible to notice some changes in the region around 998 cm −1 with the addition of PIL, due to the CH vibration of the PIL’s backbone. Around 1421 cm −1 ,there is also a characteristic vibration of PIL corresponding to -CH in–plane bending [ 49 ].…”
Section: Resultsmentioning
confidence: 99%